Pelatihan Membuat Telur Asin Rempah Produk Rumahan Berbasis UMKM di Kelurahan Mekar Jaya, Kota Depok - Sova, Maya; Yulianti, Sri; Hammad, Hammad; Indrajaya, Titus; Suryani, Mei; Suryanih, Suryanih; Agustin, Dinni (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2026)
Salted herbal eggs are a traditional processed food product with significant economic potential to be developed as a home-based micro, small, and medium enterprise (MSME). This community service program aimed to enhance the knowledge and skills of the residents of Mekar Jaya Village, Depok City, in producing high-quality herbal salted eggs as a viable home industry product. The program involved 52 participants consisting of housewives, youth organization members (Karang Taruna), and MSME actors. The implementation methods included lectures, demonstrations, hands-on practice, and evaluation using pre-test and post-test instruments. The results showed a significant improvement in participants’ knowledge across several aspects, including production techniques, food hygiene, marketing strategies, and basic financial management. The highest improvement was observed in marketing and branding competencies. Post-training monitoring indicated that 88% of participants successfully initiated small-scale production and were able to market their products locally through both offline and online channels. This program demonstrates that practice-based training combined with continuous mentoring is effective in empowering communities and fostering the development of sustainable MSMEs. The findings are expected to contribute to local economic development and provide a replicable model for community-based entrepreneurship programs